Teoria dydaktyczna a praktyka nauczania-uczenia się literatury = Literature didactics versus literature teaching (learning practice) - Pasterniak, Wojciech (1935-2018) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the above paper the author is preoccupied with the analysis of the relationships between the didactic theories and the practice of teaching and learning literature. The basis for these considerations is constituted by the assumption of independence (autonomy) of literature didactics as a science having its own subject and own methods of research, and using the advances not only in the literatury sciences but also in a great many other scientific disciplines.
Keywords: dydaktyka literatury; teoria nauczania literatury; praktyka uczenia się literatury